Epidemiology of ophthalmooncology among the adult population of the Nizhny Novgorod Region - M. A. Golovanova; S. V. Saakyan; A. N. Denisenko (Опухоли головы и шеи)
The study objective is to estimate the prevalence of different tumors of the visual organ among the adult population of the Nizhny Novgorod Region.Materials and methods. Epidemiological study was conducted on the basis of a retrospective analysis of medical documents of 1601 patients over 18 years of age, both sexes and different age groups receiving treatment and diagnostic measures in the period from 2008 to 2017.Results. It was found that the share of benign tumors accounted for 64.08 %, and malignant – 35.92 %. The most common tumors of the eyelids, epithelial benign diseases account for 25.23 %. Among tumors of the uveal tract (21.17 %) malignant neoplasms in the choroid are 10.68 %.Conclusion. In the structure of oncopathology of the population of the Nizhny Novgorod Region, eyelid tumors are common, most of which are of epithelial origin. Among the neoplasms of the uveal tract malignant neoplasms of the choroid prevail.